The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/molecules23020269
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression Analysis and Functional Characterization of Squalene Synthase (SQS) from Tripterygium wilfordii

Abstract: Celastrol is an active triterpenoid compound derived from Tripterygium wilfordii which is well-known as a traditional Chinese medicinal plant. Squalene synthase has a vital role in condensing two molecules of farnesyl diphosphate to form squalene, a key precursor of triterpenoid biosynthesis. In the present study, T. wilfordii squalene synthase (TwSQS) was cloned followed by prokaryotic expression and functional verification. The open reading frame cDNA of TwSQS was 1242 bp encoding 413 amino acids. Bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
4
10
0
Order By: Relevance
“…Relatively, the expression level in leaves and roots was about 1.5- and 4.8-times of that in stems (Figure 6a), suggesting that MsSQS was preferentially expressed in root tissues. The result is consistent with the observations that SQS was predominantly expressed in roots of soybean and Tripterygium wilfordii [11,37].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Relatively, the expression level in leaves and roots was about 1.5- and 4.8-times of that in stems (Figure 6a), suggesting that MsSQS was preferentially expressed in root tissues. The result is consistent with the observations that SQS was predominantly expressed in roots of soybean and Tripterygium wilfordii [11,37].…”
Section: Resultssupporting
confidence: 92%
“…Some plants, such as Withania somnifera [47], Betula platyphylla [15] and Arabidopsis [22], displayed a leaf-predominant pattern, suggesting that the spatial and temporal expression patterns of SQS genes vary greatly in different plants. Consistent with the observations that the SQS transcript was activated by MeJA induction [17,18,37], MsSQS was up-regulated upon exposure to MeJA and the stimulation resulted in an increased amount of the MsSQS enzyme (Figure 6). It has been reported that the hydrophobic amino acid residues at the C-terminal of SQS contribute to the membrane anchoring function [4,5].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The farnesyl pyrophosphate synthase catalyzes DMAPP and IPP to form FPP, which is a key precursor of triterpenoids 58–60 . Squalene synthase (SQS) plays an essential role in isoprenoid biosynthesis since it converts FPP into squalene 61 . The next enzyme, squalene epoxidase (SQE), which is also known as squalene monooxygenase, converts squalene into 2,3‐oxidosqualene with the participation of NADPH‐cytochrome P450 reductase 62 .…”
Section: Biosynthesismentioning
confidence: 99%